Impact of maritime logistics on archipelagic economic development in Eastern Indonesia - Chairullah Amin; Heti Mulyati; Eva Anggraini; Tridoyo Kusumastanto (Asian Journal of Shipping and Logistics (AJSL), 2021)
The efficiency of logistics is a determinant in developing trade cooperation between regions. Many areas in the eastern part of Indonesia have a flawed logistics system that results in a low level of competitiveness. The paper analyses local ports' performance and maritime logistics impact on the small island economy in East Indonesia, especially in the North Maluku Province. The research method used the survey and the Stochastic Frontier Analysis to measure each local port's performance in which Gross Regional Domestic Product (GRDP) per capita constitutes the output variable. While GRDP, number of cargo throughput, number of port labor, inland connection, loading and unloading tariff, and sea freight cost are input variables. The results show that the loading and unloading tariffs and sea transportation costs harm the GRDP per capita of the respective small island districts. Other findings suggest that the port of Morotai, Central Halmahera, North Halmahera, and Ternate have a higher level of technical efficiency than those in East Halmahera, South Halmahera, Sula, and Tidore. Low port efficiency can disrupt the distribution of goods between islands, resulting in higher logistics costs. The limited data and the small scope of the area is the restriction of the study.
Keywords: 650; Efficiency; Local economic development; Maritime logistics; Small Islands; Stochastic frontier